Highly Pertinent Algorithm for the Market of Business Intelligence, Context and Native Advertising - Guseva, Anna I.; Kireev, Vasiliy S.; Filippov, Stanislav A. (International Journal of Economics and Financial Issues, 2016)
This article presents the study results of the business intelligence markets, the promote products on social media, and a new method for increasing the information pertinence in the scientific recommender systems, scientific information systems, analysis of the recommender systems that contain information about scientific publications, is represented. The prospects of using this method in the Business Intelligence systems, content management systems for native advertising systems to find content on the Internet and assessed the current state of the market such systems. Keywords: context and native advertising market, Business Intelligence market, highly pertinent algorithms, recommender systems JEL Classifications: A11, M30, M37